Lakon Brubuh Maèspati: Intepretasi Ulang Nilai Kesetiaan - Joko Laras Moyo (Wayang Nusantara: Journal of Puppetry, 2019)
Lakon Brubuh Maèspati: The work of the puppet performance is aimed at presenting one of the stories in the Maespati kingdom, which is rarely performed in Yogyakarta. This work is entitled Brubuh Maèspati. The play Brubuh Maèspati is a piece of the puppet plays that tells Harjunasasrabahu, Dewi Citrawati, Suwanda, and Dasamuka. The concept of sanggit of Soetarno et al. used as a framework for working on the play Brubuh Maèspati. Sanggit means the mastermind’s creativity related to interpretation and the cultivation of Pakeliran elements to achieve the aesthetic stability of puppet shows. The cultivation of Brubuh Maèspati begins with watching and reading plays related to the kingdom of Maespati. There were three plays which were chosen to be the basis for interpreting the values of loyalty, namely Actions Sumantri Ngèngèr, Dasamuka Gladhak, and Brubuh Maèspati. Then do the play, work on the characters, work on the scene, and work on musical accompaniment according to the Pakeliran structure of Yogyakarta. Brubuh Maèspati is a reinterpretation of the value of loyalty that is communicated by the plays that tell the Kingdom of Maespati.Karya pergelaran wayang ini bertujuan menyajikan kembali salah satu kisah di kerajaan Maespati, yang jarang dipergelarkan di Yogyakarta. Karya ini diberi judul Brubuh Maèspati. Lakon Brubuh Maèspati merupakan sanggit dari lakon-lakon wayang yang mengisahkan Harjunasasrabahu, Dewi Citrawati, Suwanda, dan Dasamuka. Konsep sanggit Soetarno dkk. dipakai sebagai kerangka pikir dalam menggarap lakon Brubuh Maèspati. Sanggit berarti kreativitas dalang yang berhubungan dengan penafsirandan penggarapan unsur-unsur pakeliran untuk mencapai kemantapan estetik pertunjukan wayang. Penggarapan Brubuh Maèspati dimulai dengan menonton dan membaca lakon-lakon yang berhubungan dengan kerajaan Maespati. Ada tiga lakon yang dipilih menjadi landasan dalam menafsir nilai kesetiaan yaitu lakon Sumantri Ngèngèr, Dasamuka Gladhak, dan Brubuh Maèspati. Selanjutnya dilakukan garap lakon, garap tokoh, garap adegan, dan garap iringan karawitan sesuai dengan strukturpakeliran Yogyakarta. Brubuh Maèspati merupakan interpretasi ulang nilai kesetiaan yang dikomunikasikan oleh lakon-lakon yang mengisahkan Kerajaan Maespati.